ORGANIZATION AND PROFESSIONALISM COMMITMENT AGAINST AUDITOR PERFORMANCE - Widia Astuty (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2016)
This research is intended to prove empirically: (1) The influence of organizational commitment on the auditor performance; (2) The influence of professionalism on the auditor performance; (3) The influence of organizational commitment and professionalism on the auditor performance.In this research, to get the accurate result, the writer uses associative approach. The population in this study are all auditors working in the public accounting firm in North Sumatra while sampling is saturated sample. While technique in collecting data, it is used directly questionnaire to respondents, and the method of data analysis is multiple linear regression.The result shows that: (1) organizational commitment significantly influences the performance of the auditor, (2) professionalism also influences the auditor performance, (3) organizational commitment and professionalism also give a great effect on the auditor performance. Keywords: Organizational Commitment, Professionalism, Auditor Performance